Rupa & karakter wayang purwa : Dewa Ramayana-Mahabharata / Heru S. Sudjarwo, Sumari, Undung Wiyono ; editor, Syafruddin Azhar, Tri Wibowo B.S., Ahmad Kasyful Anwar ; ilustrasi, Bambang Suwarno. - HERU S. SUDJARWO; Ahmad Kasyful Anwar; Bambang Suwarno; Sumari; Syafruddin Azhar; Tri Wibowo B.S.; Undung Wiyono (Prenada Media Group, 2010)
xxxvii, 1169 hlm. ilus. 24 cm + CD (3 eks.)